New records on autogenic behavior among populations of Ornithodoros fonsecai (Labruna and Venzal, 2009) (Ixodida: Argasidae) from northeastern Brazil - Castro-Santiago, Ana Carolina [UNESP]; Lima-Duarte, Leidiane; Camargo, Jaqueline Valeria [UNESP]; Simons, Simone Michaela; Bassini-Silva, Ricardo; Calchi, Ana Cláudia [UNESP]; de Oliveira, Glauber Meneses Barboza; Horta, Maurício Cláudio; Muñoz-Leal, Sebastián; Labruna, Marcelo Bahia; André, Marcos Rogério [UNESP]; Machado, Rosangela Zacarias [UNESP]; et al. (Springer Nature, 2025)
Ornithodoros fonsecai is an argasid tick that is endemic to Brazil. The autogeny (the oviposition without a blood meal) can be facultative or obligatory in female ticks of the family Argasidae. The present study reports new records on the facultative autogeny among populations of O. fonsecai from the states of Ceará and Pernambuco, northeast Brazil. The specimens obtained were fed on rabbits and kept in a biological oxygen demand (BOD) at 25 °C ± 1 ºC. All females obtained from both populations emerged from nymphs of third instar (N3) were autogenic, which were fed once before molting. Approximately 183 eggs were observed between 22 and 29 days (oviposition period), with a hatching rate of larvae of 52%, from two females of Ceará, and around 367 eggs between 20 and 35 days, with 92% of hatching of larvae, from three females of Pernambuco. Previously, this behavior has already been registered only in a population in the municipality of Nobres, state of Mato Grosso, Brazil. Thus, the present study reports facultative autogeny in females of O. fonsecai among populations from the states of Ceará and Pernambuco in northeastern Brazil.
Keywords: Argasid ticks; Brazilian distribution; Reproductive strategies; Soft tick